FAKTOR- FAKTOR YANG MEMPENGARUHI PENERIMAAN RETRIBUSI SAMPAH DI KABUPATEN BADUNG - Jaya, I Nengah; Sri Budhi, Made Kembar; Marhaeni, A.A.I.N (Buletin Studi Ekonomi; VOL.19.NO.2.AGUSTUS 2014.(PP 119-211), 2016)
Factors Affecting the Garbage Retribution Revenue of Badung District. The purpose of this study was to determine the factors that have impact to  the garbage retribution revenue of Badung District. The data used is primary data from questionnaires. The analysis technique used is descriptive analysis and path analysis. Variable used is the level of quality of service, ability to pay, garbage levy rates, willingness to pay, garbage levy receipts. The results of this study indicate that the level of quality of service, ability to pay,  and garbage levy rates simultaneously have positive and significant effect on WTP trash and positive and significant impact on the acceptance of waste retribution. The quality of service levels directly influence the acceptance of waste retribution and indirect influence through the willingness to pay of garbage. Ability to pay, levy rate has a direct influence on the acceptance of waste retribution and not directly through the willingness to pay significantly garbage   Keywords : quality of service level, ability to pay, willingness to pay, rates and rubbish retribution receipts
Keywords: quality of service level, ability to pay, willingness to pay, rates and rubbish retribution receipts